Bias-Based Policing: Voices from Within (Global Journal of Human-Social Science, 2013)
The popularity of the terms racial profiling and bias-based policing over the past few decades has provoked a great interest and curiosity among researchers and practitioners. Initially, studies are conducted from subaltern perspective by analyzing disparity in traffic stops; recently scholars twisted towards police perspective and started striving to understand bias in broader aspects of police-public interactions. In our study on 411 police officers, 30% admitted the prevalence of bias in their department, 40 % acknowledged the prevalence in the greater state of Alabama and further analysis revealed a scarlet differences among black and white officers and officers holding non-management and management positions.
Keywords: biased policing; police perspective; subaltern perspective; racial profiling